Reconstruction of the Authority of General Court Judges in Filling Legal Vacuum as an Effort to Strengthen Legal Certainty and Substantive Justice - Ismu Bahaiduri Febri Kurnia; Riswadi (Indonesian Journal Publisher, 2026)
In order to improve the balance between substantive justice and legal certainty in the Indonesian legal system, this study attempts to rebuild the power of general court judges to close legal gaps. In contrast to Article 24, paragraph 1 of the Republic of Indonesia's 1945 Constitution and Article 5, paragraph 1 and Article 10, paragraph 1 of Law Number 48 of 2009 concerning Judicial Power, judges have the normative legitimacy to investigate the legal values that exist in society rather than rejecting cases because the law is unclear or nonexistent. However, in practice, there are no systematic parameters regarding the limits of judicial discretion and methodological standards for legal discovery, thus potentially giving rise to inconsistencies and disparities in decisions. The study employs a normative juridical method with a statutory and analytical approach to examine normative construction, theoretical and practical problems, and formulate a model for reconstructing judges' authority based on the constitution, proportionality, and accountable legal arguments. The research findings indicate that more structured normative parameters and methodological guidelines must ensure that filling legal gaps remains within the framework of legislative supremacy and achieves substantive justice consistently and measurably.